Effects of Carbon Sources on Heterotrophic Nitrification and Glyoxylate Cycle by Alcaligenes faecalis C16 - An, Hua; Liu, Yuxiang; Wang, Yao (Asian Journal of Chemistry, 2014)
To obtain a better insight into the relationship between heterotrophic nitrification and glyoxylate cycle by heterotrophic nitrification bacterium, the two key enzymes of glyoxylate cycle, the ammonium removal ability, and the specific nitrifying activity of Alcaligenes faecalis C16 grew with different carbon sources were examined. The growth and ammonium removal ability of heterotrophic nitrification bacterium are strongly influenced by carbon sources, as well as the activities of key enzymes of glyoxylate cycle. Strain C16 grew best in the medium with fumaric acid, and failed to grow on the medium with sucrose, glycerol, glucose or ethanol as sole carbon source. There was a well correlation between the ammonium removal rate and the growth of heterotrophic nitrification bacterium. The strain C16 showed the most activities of isocitrate lyase and malate synthase when the ammonium removal rate reached highest. The results showed that the ammonium removal rate is strictly dependent on the growth of heterotrophic nitrification bacterium, and the growth of strain was strongly influenced by the glyoxylate cycle, the positive correlation relationship was found between the glyoxylate cycle and nitrification.